Britain's soldiers : rethinking war and society, 1715-1815 - Linch, Kevin, 1974-; McCormack, Matthew (Eighteenth-century worlds., 2014)
This collection examines the British Army's part-time and auxiliary forces of the Georgian period, as well as looking at the men both during their service and once they had been discharged.